2002
DOI: 10.1046/j.1365-2036.2002.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low‐dose clarithromycin triple therapy and tinidazole‐containing triple therapy for Helicobacter pylori eradication

Abstract: Background: Proton pump inhibitor‐based triple therapies are recommended as the first‐line treatment for Helicobacter pylori eradication. Aim: To evaluate the efficacies of low‐dose clarithromycin triple therapy and tinidazole‐containing triple therapy in a metronidazole resistance prevalent area and to compare the efficacies with standard triple therapy. Methods: In a randomized, multicentre, prospective study, a total of 352 patients with duodenal ulcer or non‐ulcer dyspepsia were randomly divided into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
0
8
1
2
Order By: Relevance
“…It may be possible that the longer duration of treatment raises the eradication rate, but if the cause of treatment failure is antibiotic resistance, the extension of treatment period is not expected to raise the eradication rate. In this study, H. pylori eradication rate of PAC7 group did not show significant difference when compared with the recent trial conducted in Korea [17]. Previous study that compared the efficacies of omeprazolecontaining triple regimen (omeprazole 40 mg + amoxicillin 2000 mg + clarithromycin 1000 mg/day) continued for 7, 10, or 14 days did not show any difference in eradication rates, with increasing trend of poor compliance as treatment period was extended [18].…”
Section: Discussioncontrasting
confidence: 74%
“…It may be possible that the longer duration of treatment raises the eradication rate, but if the cause of treatment failure is antibiotic resistance, the extension of treatment period is not expected to raise the eradication rate. In this study, H. pylori eradication rate of PAC7 group did not show significant difference when compared with the recent trial conducted in Korea [17]. Previous study that compared the efficacies of omeprazolecontaining triple regimen (omeprazole 40 mg + amoxicillin 2000 mg + clarithromycin 1000 mg/day) continued for 7, 10, or 14 days did not show any difference in eradication rates, with increasing trend of poor compliance as treatment period was extended [18].…”
Section: Discussioncontrasting
confidence: 74%
“…A majority of the larger studies have used higher antibiotic dosages than ours, leading to higher treatment costs for the patients. In spite of the different designs, most studies have reported eradication rates around 90%, 23 , 24 with the exception of an open, non‐controlled study from Brazil, which used the same regimen as ours and reported an eradication rate of only 65% 25 . A recent, non‐blind trial from Vietnam found an eradication rate of 91% with a regimen of amoxicillin, clarithromycin and omeprazole for 10 days 26 .…”
Section: Discussionmentioning
confidence: 65%
“…However, recent studies suggest that [36] mechanisms other than age, i.e. a stronger synergism of clarithromycin plus metronidazole, even at low doses, than of clarithromycin plus amoxicillin, may be involved in the therapeutic response of PPI-based triple therapies [42,43].…”
Section: Treatmentmentioning
confidence: 99%